Efek Penambahan Eko-Enzim Dalam Air MinumTerhadap Bobot Telur, Tebal Kerabang Dan Warna Kuning Telur Ayam IPB-D1 - Nepa, Juliana Monika; Pamungkas, Aditya; Widu, Asri Apriana (CV. SINAR HOWUHOWU, 2025)
The purpose of this study was to analyze the effect of adding eco-enzyme in drinking water on egg weight, shell thickness and yolk color of IPB-D1 chicken eggs. The chickens used in this study were 96 (72 females and 24 males). The method used was a completely randomized design consisting of 4 treatments and 6 replications, each replication consisting of 4 chickens (1 male, 3 females). The treatments given were: P1 = drinking water without eco-enzyme (control), P2 = 1 Cc eco-enzyme/L drinking water/3 days, P3 = 2 Cc eco-enzyme/L drinking water/3 days, P4 = 3 Cc eco-enzyme/L drinking water/3 days. The number of eggs used to observe the quality of the egg interior was 72 eggs, 6 eggs for each treatment, and 3 replications. The results of statistical analysis showed that the treatment had a significant effect (P <0.05) on egg weight, shell thickness. The treatment did not significantly affect (P>0.05) the color of the egg yolk. The conclusion is that the addition of eco-enzyme in drinking water with a dose of 2 Cc/L of drinking water/3 days can increase the egg weight and shell thickness of IPB-D1, but does not affect the color of the egg yolk.